The Victim–Offender Relationship and Police Charging Decisions for Juvenile Delinquents: How Does Social Distance Moderate the Impact of Legal and Extralegal Factors? - Rollwagen, Heather (Youth violence and juvenile justice, 2018)
While research has established how victim-offender relationship (social distance) relates to police decision-making, comparatively little research has examined this relationship among juvenile delinquents. This article examines how the social relationship between victim and offender has a main and moderating relationship with police charging decisions among juvenile delinquents in Canada. Incidents recorded using the Uniform Crime Reporting Incident-Based Survey (N = 130,090) are modeled using logistic regression to predict the odds of police laying a charge. Independent variables include nature of the victim-offender relationship as well as demographic, geographic, and offense-specific variables. Main effects models show that incidents involving current intimate partners are most likely to result in arrest, followed by incidents involving strangers. Importantly, stratified models suggest that social distance conditions how other legal and extralegal factors relate to police arrest decisions. Similar to the adult offending population, victim-offender relationship shapes the way criminal incidents are officially addressed in complex ways.